BS IEC 61031. Nuclear facilities. Instrumentation and control systems. Design, location and application criteria for installed area gamma radiation dose rate monitoring equipment for use during normal operation and anticipated operational occurrences. (22nd October 2019) - British Standards Institution,
No abstract available